Aspectos de um trickster ? Um estudo comparativo sobre Loki na Edda em prosa e Edda poética - Melo, Glezia Alves de (2023)
Loki is considered one of the most emblematic, chaotic and allegorical figures in 13th century narratives, presenting several challenges to its possible understandings in the study of Norse mythology. The objective of this research aimed to analyze the ancient (pre-Christian) primary sources and compare them with the sources of Snorri's Edda with the aim of understanding the mechanisms of the myth transmitted in society about the divinity of pre-Christian Loki in its multiple variations: his individual actions and with the other gods within the myth, with the aim of listing the main mythological, historical-cultural aspects and in the context of pre-Christian society about the similarities in the attitudes of this deity. With this, the approximations of his characteristics within the primary sources were listed and the most recent mythographic analyzes were encouraged, aiming to cover how aspects of the roles of this mythical figure overlap between the classical sources (Eddas) and contemporary studies (mythographies). Offering as a presupposition, the methodological material presented by Schjødt with the essential criticisms and notes on the comparative (qualitative) mechanism within the analyzes of Loki's mythical narratives. Above all, specifically, we used the methodology of the author of the comparison in its internal form, therefore, Loki was compared with the elements within the worldview, that is, within the pre-Christian imaginary. With this, we propose a demonstration of the visuality of the pre-Christian mythical aspects of his divinity and some recent understandings about Loki being presented as descriptive elements in the comparative analysis linking these points within the relationships with society, which shapes the myth.